Design of Single Mode Fiber for Optical Communications - Salih, Aqeel R. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2020)
In this work, a step-index fiber with core index  and cladding index  has been designed. Single-mode operation can be obtained by using a fiber with core diameters 4â€“13 Âµm operating at a wavelength of 1.31 Âµm and by 4â€“15 Âµm at 1.55 Âµm. The fundamental fiber mode properties such as phase constant, effective refractive index, mode radius, effective mode area and the power in the core were calculated. Distributions of the intensity and the amplitude were shown.